(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2021)
This article was prepared from the conference that the author gave at the opening of ANIMA UDESC - Internacional Seminar of Studies in the Arts of Puppetry - Online Edition, on May 21, 2021. The conference had as its theme Training experiences in cyberspace and creative processes in social isolation, and addressed aspects of the link between Puppet Theater and the pandemic, and reflections based on the author’s work with her students in the first six months of the pandemic.